DIFFERENT ATTITUDES REGARDING THE IMPLEMENTATION OF THE COVID-19 HEALTH PROTOCOL IN TYPE 2 AND NON-DIABETES MELLITUS PATIENTS. - Syahniar, Rike; Putri, Annisa Gholiza (Politeknik Kesehatan Makassar, 2022)
Background: Patients with diabetes mellitus (DM) have a poor prognosis if infected with Coronavirus Disease 2019 (COVID-19). Diabetes is associated with increased severity and mortality of COVID-19 disease. Therefore, it is essential for people with diabetes to implement health protocols not to contact SARS-CoV-2, which causes COVID-19.Objective: The purpose of this study was to determine differences in the behavior of implementing the Covid-19 health protocol in patients with type 2 DM and non-DM.Methods: This research is an observational analytic with a cross-sectional approach involving DM and non-DM patients at the Indramayu Regional General Hospital. The research instrument used was a questionnaire and medical record data. P-value <0.05 means statistically significant Results: A total of 120 subjects consisting of 60 patients with type 2 DM and 60 non-DM were willing to participate in the study. Fifty-five people (91.7%) type 2 DM patients and 53 people (88.3%) non-DM patients applied the Covid-19 health protocol behavior with good categories. The results of the Mann-Whitney test show that there are differences in the conduct of implementing the Covid-19 health protocol in patients with type 2 diabetes mellitus and non-diabetes Mellitus at Indramayu Hospital (p-value = 0.000). Conclusion: We conclude that type 2 DM patients are more concerned about preventing the transmission of COVID-19 through good behavior in implementing the COVID-19 health protocol.